THE EXPERIENCE OF TELEHEALTH IN THE SUS FROM THE PERSPECTIVE OF SPECIALIZED CARE PROJECTS - Silva, Douglas Pereira; da Silva Figueiredo Matos, Eduardo Henrique; de Paula, Lucas Gomes Costa; de Paiva, Tais Milene Santos; Soares, Luana Mesquita; da Silva, Marcos Filipe (Editora Impacto Científico, 2025)
This article evaluates a telemedicine model implemented in Intensive Care Units (ICUs) nationwide through the Proadi SUS program of the Ministry of Health. The project involved a partnership with five Excellence-Recognized Health Entities (ESRE): HIAE, HAOC, BP, HCor, and HSL. The goal was to share expertise with professionals in public ICUs facing a shortage of specialists. The methodology included telerounds conducted by multidisciplinary teams and setting care goals recorded digitally. Results showed a significant increase in televisits and a reduction in the standardized mortality rate from 1.41 to 1.13. It concludes that telemedicine improved access and quality of intensive care, aligning with the Ministry of Health's Strategic Vision for Digital Health.DOI: 10.56238/edimpacto2025.060-009